A Study on the Revenue Generation Trend of Thiruvallur and Thiruttani Taluks (Viz., Thiruppasur, Siruvanoor, Thiruvallur and Agoor and Pattabiramapuram Villages of Thiruttani) of Tamil Nadu+ (Global Journal of Human-Social Science, 2021)
Tamilnadu is one of the economically developed states in India which has 32 districts taluks in hundreds and villages in thousands But lots of studies on Tamilnadu s regional development have found a wide disparity in economic development across the state The North part of Tamilnadu is a comparatively backward region in general and the districts like Dharmapuri Villupuram Tiruvannamalai and Thiruvallur in particular As a result it is of special importance and essential to review the rural local bodies finances with reference to backward district in general and Thiruvellur district in particular in the wake of 73rd constitutional amendment